Prototype Project SCADA on Hemodialysis Mixing Tank Operation - Dede Furqon Nurjaman (Universitas Multimedia Nusantara, 2021)
Pharmaceutical companies are an example of an industrial sector that uses technology-based systems in its production process. In this research the author will develop a SCADA (Supervisory Control Acquisition Data) system as a platform to solve several problems that are present in pharmaceutical production, namely in the drug production process using hemodilysis mixing tanks. The method that the author uses for this research is experimental research and data collection methods, which use the independent variables of the study, water level control and temperature control, while the independent variables related to the system reading results are displayed on the SCADA screen. Based on the results of mathematical calculations, it can be concluded that the production process using the SCADA system produces a more efficient time with a total time difference of 38 minutes/batch. Operations using SCADA technology within 24 hours were able to produce 4 batches of Infusion Bags, while using the conventional system only 3 batches. Operational needs using SCADA technology will generate more benefits in terms of cost and time, creating more effective and efficient work system for the company.